THE EFFECT OF ROUND ROBIN TYPE COOPERATIVE LEARNING METHOD ON THE ABILITY OF SPEAKING SKILLS IN ELEMENTARY SCHOOL LINGUISTIC ASPECTS - Kornelia Septiana Kusuma; Cholifah Tur Rosidah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This study aims to determine whether there is an effect on the speaking skills of fifth-grade elementary school students. This research uses a quantitative approach with a Pre-Experimental design in the form of a one-group pretest-posttest design. The respondents of this study were 25 children. The method used in data collection is the assessment of pretests and posttests, the results of which will be compared later. The data analysis technique used is descriptive quantitative, using descriptive analysis tests, normality tests, and paired samples tests. Based on the results of tests using SPSS, the difference in average pretest and posttest scores is known. Thus, the proposed hypothesis is tested by data showing that there is an effect of the Round Robin learning method on the speaking skills in the language aspects of elementary school students